3D computer simulation of roundhouse kick in taekwondo - Kim, Y. K.; Yamaguchi, G. T.; Hinrichs, R. N. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Trunk rotation was found to be the most important factor for producing foot speed in roundhouse kick. However, without also increasing hip flexor torque the increased trunk rotation torque produces a kick at the wrong height.